HC-SCR catalyst and preparation method and application thereof

By introducing Ce elements into the HC-SCR catalyst and combining the ZSM-5 support, the problems of low catalyst efficiency and narrow temperature window are solved, and more efficient NOx and HC removal capabilities and a wider applicable temperature range are achieved.

CN119771486AActive Publication Date: 2025-04-08TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411893595.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-08
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing HC-SCR catalyst has low catalytic efficiency and a narrow temperature window, so it cannot be effectively used in specific operating conditions.

Method used

The ZSM-5 support is used to combine with MnCeOx active components, and the low-temperature conversion rate of the catalyst is improved and the temperature window is widened by the introduction of Ce elements, and the active components are prepared by MOF derivatization method and solid phase grinding method to improve their loading and dispersion.

Benefits of technology

The low-temperature conversion and temperature window of HC-SCR catalyst are significantly improved, the oxygen mobility and surface acidity of the catalyst are improved, and the removal ability of NOx and HC is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771486A_ABST
    Figure CN119771486A_ABST
Patent Text Reader

Abstract

The invention provides an HC-SCR catalyst and a preparation method and application thereof, the HC-SCR catalyst comprises a carrier and an active component loaded on the carrier, the carrier is a ZSM-5 carrier, and the active component is MnCeOx. The HC-SCR catalyst has the beneficial effects that the second active element Ce is introduced on the basis of a manganese-based molecular sieve catalyst, so that the conversion rate of the HC-SCR catalyst at low temperature is further improved, and a temperature window is widened. Due to the introduction of Ce, the reduction temperature can be reduced, and the oxidation-reduction performance of the catalyst is promoted; richer sites are provided for activation of propylene, and further reaction of active intermediate products is promoted; according to the present invention, the active component of the catalyst is prepared by using the MOF derivation method, the particle size of the active component prepared by using the method is uniform, the valence state of the Mn ion is improved, and the formation of Mn < 3 + > is promoted; and the active components of the catalyst prepared by the solid-phase grinding method are highly dispersed on the surface of the catalyst, so that the loading capacity of the active components is ensured to a great extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of catalyst technology, and specifically relates to an HC-SCR catalyst and a preparation method and application thereof. Background Art

[0002] As an important part of the steel industry, the coking industry produces a large amount of pollutants during the production process, especially the coke oven flue gas emitted during the coking process contains NO x 、SO 2 , volatile organic compounds (VOCs) and particulate matter. x The selective catalytic reduction of ammonia (NH 3 -SCR) process requires supplementary heat to the flue gas due to the high temperature range of the optimal efficiency of vanadium-based catalysts. A large amount of reducing agent NH 3 , increasing the extra cost of purchase and storage. At the same time, VOCs in the coking process are usually removed by combustion. Therefore, the original VOCs in the flue gas are used as reducing agents for NO x HC-SCR, which is derived from the removal of HC, has become a hot topic of concern. The preparation and selection of high-performance catalysts in the HC-SCR process has become the focus of research.

[0003] In practice, HC-SCR catalysts are used to remove NO from flue gas. x and C 3 H 6 However, this type of catalyst has problems such as low catalytic efficiency and narrow temperature window when used, which makes it impossible to apply it to specific working conditions. Summary of the invention

[0004] The purpose of the present application is to provide a HC-SCR catalyst and a preparation method and application thereof, aiming to solve the problems of low catalytic efficiency and narrow temperature window of existing HC-SCR catalysts.

[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows: In a first aspect of the present application, a HC-SCR catalyst is provided, comprising a carrier and an active component supported on the carrier, wherein the carrier is a ZSM-5 carrier, and the active component is MnCeO x Wherein, X can be 2, 3, 4, 5, 6 or 7.

[0006] This application introduces a second active element Ce on the basis of a manganese-based molecular sieve catalyst, further improving the conversion rate of the HC-SCR catalyst at low temperatures and widening the temperature window. Specifically, the introduction of the Ce element increases the adsorbed oxygen content on the catalyst surface, accelerates the oxygen migration on the catalyst surface, and is beneficial to the oxidation reaction of HC. The introduction of Ce can also reduce the reduction temperature and promote the redox performance on the catalyst. At the same time, the dual-active metal catalyst has higher surface acidity, especially weak proton acid (Bronsted) acid sites, which provide more abundant sites for the activation of propylene and promote the further reaction of active intermediates.

[0007] According to some embodiments of the HC-SCR catalyst described in the present application, the active component is Mn 0.32 Ce 0.08 O X , where 0.5≤X≤7. For example, X is 2, 3, 4, 5, 6 or 7.

[0008] According to some embodiments of the HC-SCR catalyst described in the present application, the molar ratio of the carrier to the active component is (4-10):2, for example, 4:2, 5:2, 6:2, 7:2, 8:2, 10:2, etc.

[0009] The second aspect of the present application provides a composition for preparing the HC-SCR catalyst described in the first aspect of the present application, comprising a manganese source, a cerium source, terephthalic acid, a ZSM-5 molecular sieve and a solvent.

[0010] According to some embodiments of the composition described herein, the manganese source includes a 50 wt % manganese nitrate solution.

[0011] According to some embodiments of the composition described herein, the cerium source includes cerium nitrate hexahydrate with a purity of 99.5%.

[0012] According to some embodiments of the composition described herein, the purity of the terephthalic acid is 99%.

[0013] According to some embodiments of the composition described herein, the solvent includes one or both of N,N-dimethylformamide and anhydrous ethanol.

[0014] According to some embodiments of the composition described in the present application, the molar ratio of the manganese source to the cerium source is (1-7):1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, etc.

[0015] According to some embodiments of the composition described in the present application, the molar ratio of the total molar amount of the manganese element and the cerium element to the terephthalic acid is 1:(1.0-1.4), for example, 1:1, 1:1.2, 1:1.3, 1:1.4, etc.

[0016] According to some embodiments of the composition described in the present application, the molar ratio of the manganese source to the ZSM-5 molecular sieve is (2-6):10, for example, 2:10, 3:10, 4:10, 6:10, etc.

[0017] According to some embodiments of the composition described in the present application, the molar ratio of the manganese source to the solvent is 1:(120-170), for example, 1:120, 1:130, 1:150, 1:160, 1:170, etc.

[0018] According to some embodiments of the composition described in the present application, the solvent is a mixture of N,N-dimethylformamide and anhydrous ethanol. Preferably, the molar ratio of N,N-dimethylformamide to anhydrous ethanol is 125:41.

[0019] The third aspect of the present application provides a method for preparing the HC-SCR catalyst described in the first aspect of the present application, which is prepared using the composition described in the second aspect of the present application.

[0020] According to some embodiments of the preparation method described in this application, the following steps are included: (1) mixing the manganese source, the cerium source, the terephthalic acid and the solvent, reacting the mixture, and calcining the reaction product to obtain the active component MnCeO X , 0.5≤X≤7.

[0021] (2) The active component and ZSM-5 molecular sieve are mixed and ground to obtain the HC-SCR catalyst.

[0022] The active component described in the present application is prepared by MOF derivatization method. The active component prepared by this method has uniform particle size, and at the same time improves the valence state of Mn ions, promotes Mn 3+ The formation of Mn 3+ It is not only an active site for NO oxidation, but also has certain reducing properties.

[0023] The active components and carriers described in the present application are combined by solid phase grinding. The active components of the catalyst prepared by the solid phase grinding method are highly dispersed on the catalyst surface, which largely ensures the loading amount of the active components.

[0024] Mn 3+ It is the active site that plays a leading role in the HC-SCR reaction, that is, the active site for NO oxidation, and has certain reduction performance. The rich Mn 3+ The active sites are conducive to the generation and reaction of a large number of intermediates, promoting the HC-SCR reaction. The surface active oxygen is generated by oxygen defects (oxygen vacancies), including peroxides (O - ) and superoxide (O2- ) species, which is beneficial to the oxidation of NO to NO on the catalyst surface 2 The process and the x H y O z At the same time, surface active oxygen has a higher oxygen mobility than other oxygen species and is therefore more active in redox reactions, which is beneficial to improving the conversion rate of the catalyst and broadening the temperature window of the catalyst.

[0025] This application uses MOF derivatization to prepare active components to improve the valence state of Mn ions and promote the 3+ At the same time, the active components are loaded on the carrier to a large extent through solid phase grinding, avoiding the loss of active components. The introduction of Ce increases the oxygen content adsorbed on the catalyst surface, accelerates the oxygen migration on the catalyst surface, and is beneficial to the oxidation reaction of HC. Ce can also reduce the reduction temperature and increase the surface acidity of the catalyst, providing more abundant sites for the activation of propylene and promoting the further reaction of active intermediates.

[0026] According to some embodiments of the preparation method described in the present application, in step (1), the reaction temperature is 95-120°C, for example, 95°C, 100°C, 105°C, 110°C, 120°C, etc., and the reaction time is 10-14h, for example, 10h, 12h, 13h, 14h, etc.

[0027] According to some embodiments of the preparation method described in the present application, the calcination includes a first stage calcination and a second stage calcination, the first stage calcination is in a nitrogen atmosphere, at a temperature of 300-400°C, such as 300°C, 320°C, 340°C, 360°C, 400°C, etc., for 2-4h, such as 2h, 3h, 4h, etc.; the second stage calcination is in an air atmosphere, at a temperature of 300-400°C, such as 300°C, 320°C, 340°C, 360°C, 400°C, etc., for 2-4h, such as 2h, 3h, 4h, etc.

[0028] According to some embodiments of the preparation method described in the present application, the second stage calcination is performed after the first stage calcination is completed and cooled to room temperature.

[0029] According to some embodiments of the preparation method described in the present application, the heating rate of the first stage calcination is 5°C / min.

[0030] According to some embodiments of the preparation method described in the present application, the heating rate of the second stage calcination is 2°C / min.

[0031] According to some embodiments of the preparation method described in the present application, the grinding is carried out in an agate mortar.

[0032] According to some embodiments of the preparation method described in the present application, the grinding time is 30-60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 60 min, etc.

[0033] The fourth aspect of the present application provides a method for treating coke oven flue gas, which is carried out under the action of the HC-SCR catalyst described in the first aspect of the present application or the HC-SCR catalyst obtained by the preparation method described in the third aspect of the present application.

[0034] According to some embodiments of the method for treating coke oven flue gas described in the present application, the coke oven flue gas includes NO, NO 2 and C 3 H 6 One or more of.

[0035] According to some embodiments of the method for treating coke oven flue gas described in the present application, the reaction temperature is 150-350° C., for example, 150° C., 180° C., 200° C., 250° C., 300° C., 250° C. The reaction temperature range described in the present application is consistent with the flue gas temperature of 180-250° C. in the coke oven flue gas of a coking plant, and the catalyst described in the present application has a wider temperature window, which further enables the catalyst to have better adaptability.

[0036] According to some embodiments of the method for treating coke oven flue gas described in the present application, the volume space velocity of the coke oven flue gas is 25000-35000 / h, for example, 25000 / h, 28000 / h, 30000 / h, 32000 / h, 35000 / h, etc.

[0037] The beneficial effects of this application include: (1) The catalyst described in the present application introduces a second active element Ce on the basis of a manganese-based molecular sieve catalyst, further improving the conversion rate of the HC-SCR catalyst at low temperatures and widening the temperature window. Specifically, the introduction of the Ce element increases the adsorbed oxygen content on the catalyst surface, accelerates the oxygen migration on the catalyst surface, and is beneficial to the oxidation reaction of HC. The introduction of Ce can also reduce the reduction temperature and promote the redox performance of the catalyst. At the same time, the dual-active metal catalyst has higher surface acidity, especially weak Bronsted acid sites, which provide more abundant sites for the activation of propylene and promote the further reaction of active intermediates.

[0038] (2) The active component of the catalyst described in this application is prepared by MOF derivatization method. The active component prepared by this method has uniform particle size and improves the valence state of Mn ions, promoting the 3+ The formation of Mn 3+It is not only an active site for NO oxidation, but also has certain reduction performance; and the active components of the catalyst described in the present application are combined with the ZSM-5 molecular sieve by a solid phase grinding method. The active components of the catalyst prepared by the solid phase grinding method are highly dispersed on the catalyst surface, which largely ensures the loading amount of the active components.

[0039] (3) The optimal temperature range of HC-SCR in the present application is consistent with the flue gas temperature of 180-250°C in the coke oven flue gas of the coking plant. The higher HC-SCR performance and wider temperature window make the catalyst in the present invention have better adaptability. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The catalysts described in Example 1, Comparative Example 1, Comparative Example 4 and Comparative Example 5 of the present application catalyze NO x The conversion efficiency diagram of Figure 2 This is a graph showing the conversion efficiency of CH catalyzed by the catalysts described in Example 1, Comparative Example 1, Comparative Example 4 and Comparative Example 5 of the present application; Figure 3 The catalysts described in Comparative Examples 1 and 2 of this application catalyze NO x The conversion efficiency diagram of Figure 4 This is a graph showing the conversion efficiency of CH catalyzed by the catalysts described in Comparative Examples 1 and 2 of the present application; Figure 5 XRD spectra of the active components of the catalyst and the catalyst described in Comparative Example 1 of the present application and the active components of the catalyst and the catalyst described in Comparative Example 2; Figure 6 (a) is the XPS spectra of Mn 2P of the catalyst described in Comparative Example 1 and the catalyst described in Comparative Example 2 of the present application; Figure 6 (b) is the XPS spectra of O 1s of the catalyst described in Comparative Example 1 and the catalyst described in Comparative Example 2 of the present application; Figure 7 (a) The catalyst described in Comparative Examples 1 and 3 of the present application catalyzes NO x The conversion efficiency diagram of Figure 7 (b) is a graph showing the conversion efficiency of CH catalyzed by the catalysts described in Comparative Examples 1 and 3 of the present application; Figure 8 (a) Mn prepared in Comparative Example 1 of the present application 0.4 -SEM image of MOF / ZSM-5-solid phase milled catalyst; Figure 8 (b) is a SEM image of the Mn0.4-MOF / ZSM-5-precipitation catalyst prepared in Comparative Example 3 of the present application; Figure 8 (c) and Figure 8 (d) is the Mn prepared in Comparative Example 1 of this application 0.4 -EDS spectrum of MOF / ZSM-5-solid phase grinding catalyst; Figure 8 (e) and Figure 8 (f) is the Mn prepared in Comparative Example 3 of this application 0.4 -EDS spectrum of MOF / ZSM-5-deposition catalyst; Figure 8 (g) and Figure 8 (h) are respectively Mn prepared in Comparative Example 1 and Example 3 of the present application 0.4 -MOF / ZSM-5-Solid Phase Grinding Catalyst and Mn 0.4 -SEM+EDS spectra of MOF / ZSM-5-deposition catalyst; Fig. 9 (a) The catalyst described in Examples 1 to 5 of the present application catalyzes NO x The conversion efficiency diagram of Fig. 9 (b) is a graph showing the conversion efficiency of CH catalyzed by the catalysts described in Examples 1 to 5 of the present application; Fig.10 (a) The catalyst described in Examples 6 to 9 of the present application catalyzes NO x The conversion efficiency diagram of Fig.10 (b) is a graph showing the conversion efficiency of CH catalyzed by the catalysts described in Examples 6 to 9 of the present application. DETAILED DESCRIPTION

[0041] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0042] The technical solution of the present application is described in detail below in conjunction with specific embodiments and drawings.

[0043] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0044] The present invention provides an HC-SCR catalyst. The catalyst is composed of the following components: Mn 0.32 Ce 0.08 O X The active component and the ZSM-5 carrier. 0.32 Ce 0.08 O X The active component is prepared by MOF derivatization method. The active component is loaded onto the molecular sieve carrier by solid phase grinding method. That is, the HC-SCR catalyst of the present invention is composed of MnCe-MOF / ZSM-5.

[0045] Mn 3+ It is the active site that plays a leading role in the HC-SCR reaction. It is not only the active site for NO oxidation, but also has certain reduction performance. 3+ The active sites are conducive to the generation and reaction of a large number of intermediates, which promotes the HC-SCR reaction. Surface active oxygen is generated by oxygen defects (oxygen vacancies), including peroxides (O - ) and superoxide (O 2- ) species, which is beneficial to the oxidation of NO to NO on the catalyst surface 2 The process and the x H y O z At the same time, the surface active oxygen has a higher oxygen mobility than other oxygen species, so it is more active in the redox reaction, which is beneficial to improve the conversion rate of the catalyst and broaden the temperature window of the catalyst. Specifically, the use of MOF derivatization method to prepare active components in the present invention can improve the valence state of Mn ions and promote the 3+At the same time, solid phase grinding can load the active components on the carrier to a large extent, avoiding the loss of active components. The introduction of Ce increases the oxygen content adsorbed on the catalyst surface, accelerates the oxygen migration on the catalyst surface, and is beneficial to the oxidation reaction of HC. Ce can also reduce the reduction temperature and increase the surface acidity of the catalyst, providing more abundant sites for the activation of propylene and promoting the further reaction of active intermediates.

[0046] Some examples of this application compare the HC-SCR efficiency of MnOx active component-loaded molecular sieve catalysts prepared by MOF derivatization and precipitation methods, highlighting the superiority of the active component prepared by MOF derivatization. For example: NO x The conversion rate is higher than that of Mn-C / ZSM-5 catalyst. x The highest conversion rate reached 90.37%, which is much higher than the highest conversion rate of 76.63% of Mn-C / ZSM-5 catalyst at 250°C. The higher conversion efficiency and wider temperature window indicate that Mn-MOF / ZSM-5 catalyst has better low-temperature HC-SCR performance. At the same time, the HC conversion rate of Mn-MOF / ZSM-5 catalyst reached almost 100% at 225°C.

[0047] Some examples of the present application compare the HC-SCR efficiency of molecular sieve catalysts loaded with active components by solid phase grinding and deposition precipitation, highlighting the superiority of solid phase grinding for loading active components. For example, in the entire temperature range of 150-350°C, the catalyst prepared by solid phase grinding is superior to that prepared by deposition precipitation.

[0048] Some examples of this application compare the use of Ce, La, and Pr as the second active metal element to prepare a bimetallic active component through MOF derivatization, and then load it onto a ZSM-5 carrier through solid phase grinding. The prepared catalyst has a temperature range of 150-350°C and NO x =C 3 H 6 =500 ppm, O 2 =6% and GHSV=30000 / h. x The highest conversion rate reached 97.26% at 225°C, and the HC conversion rate was greater than 90% in the entire temperature range.

[0049] Some examples of the present application compare the preparation of MnCe-MOF / ZSM-5 catalysts with different Mn and Ce ratios at a temperature range of 150-350°C and NO x =C 3 H 6=500 ppm, O 2 =6% and GHSV=30000 / h. When Mn:Ce=4:1 (molar ratio), the catalyst has the best catalytic performance and achieves the highest conversion rate of 97.26% at 225°C. The HC conversion rate is greater than 90% in the entire temperature range.

[0050] Some examples of the present application compare the preparation of MnCe-MOF / ZSM-5 catalysts with different active components and molecular sieve carriers in the temperature range of 150-350°C, NO x =C 3 H 6 =500 ppm, O 2 =6% and GHSV=30000 / h, the HC-SCR performance test was carried out. When the ratio of active component to molecular sieve carrier was 4:10, the reaction activity of the catalyst almost reached a certain peak. Because more active components cannot bring higher conversion rate and wider temperature window, in order to achieve economic benefits of the catalyst, the ratio of active component to molecular sieve was 4:1. Specific embodiment: Example 1

[0052] The second active metal element Ce was introduced on the basis of Mn-based catalyst by using MOF derivatization method to prepare bimetallic active components and solid phase grinding method to load active components.

[0053] A total of 10 mmol of Mn(NO 3 ) 3 Aqueous solution (50%) and 99.5% pure Ce(NO 3 ) 3 6H 2 O, 12.8 mmol H 2 BDC (terephthalic acid, purity 99%) was added to 96 ml N,N-dimethylformamide and 24 ml anhydrous ethanol and stirred in a beaker for 1 h to fully disperse the solution. The resulting mixed solution was placed in a 250 ml reactor and crystallized at high temperature and high pressure in an oven at 100 °C for 12 h to obtain light yellow solid particles. The resulting solid was centrifuged in a centrifuge tube for 2-3 times, and the lower layer of precipitate was washed and filtered, and repeated 3 times. The resulting precipitate was dried in an oven at 100 °C for 12 h, and then heated to 350 °C in a tube furnace at a heating rate of 5 °C / min and heated to 400 °C with N 2 Calcinate for 3 h, wait for the tube furnace to cool to room temperature, then heat up to 350 °C at a heating rate of 2 °C / min and calcine in air for 3 h. The final sample is recorded as MnCe-MOF.

[0054] MnCe-MOF and ZSM-5 molecular sieve were ground in an agate mortar at a molar ratio of 2:5 for 40 min to obtain the HC-SCR catalyst MnCe-MOF / ZSM-5.

[0055] Example 2 The difference between Example 2 and Example 1 is that: Mn(NO 3 ) 3 Aqueous solution and Ce(NO 3 ) 3 6H 2 The molar ratio of MnO was 1:1, and the other operations were the same as in Example 1. The obtained catalyst was Mn 0.2 Ce 0.2 -MOF / ZSM-5.

[0056] Example 3 The difference between Example 3 and Example 1 is that: Mn(NO 3 ) 3 Aqueous solution and Ce(NO 3 ) 3 6H 2 The molar ratio of MnO was 2:1, and the other operations were the same as in Example 1. The obtained catalyst was Mn 0.26 Ce 0.13 -MOF / ZSM-5.

[0057] Example 4 The difference between Example 4 and Example 1 is that: Mn(NO 3 ) 3 Aqueous solution and Ce(NO 3 ) 3 6H 2 The molar ratio of MnO is 3:1, and the other operations are the same as in Example 1. The obtained catalyst is Mn 0.3 Ce 0.1 -MOF / ZSM-5.

[0058] Example 5 The difference between Example 5 and Example 1 is that: Mn(NO 3 ) 3 Aqueous solution and Ce(NO 3 ) 3 6H 2 The molar ratio of MnO was 5.6:1, and the remaining operations were the same as in Example 1. The obtained catalyst was Mn 0.34 Ce 0.06 -MOF / ZSM-5.

[0059] Example 6 The difference between Example 6 and Example 1 is that: Mn(NO3 ) 3 Aqueous solution and Ce(NO 3 ) 3 6H 2 The molar ratio of MnO was 7:1, and the other operations were the same as in Example 1. The obtained catalyst was Mn 0.35 Ce 0.05 -MOF / ZSM-5.

[0060] Example 7 The only difference between Example 7 and Example 1 is that the molar ratio of MnCe-MOF to ZSM-5 molecular sieve is 2:10, and the other operations are the same as those in Example 1. The obtained catalyst is Mn 0.16 Ce 0.04 -MOF / ZSM-5.

[0061] Example 8 The only difference between Example 8 and Example 1 is that the molar ratio of MnCe-MOF to ZSM-5 molecular sieve is 3:10, and the other operations are the same as those in Example 1. The obtained catalyst is Mn 0.24 Ce 0.06 -MOF / ZSM-5.

[0062] Example 9 The only difference between Example 9 and Example 1 is that the molar ratio of MnCe-MOF to ZSM-5 molecular sieve is 5:10, and the other operations are the same as those in Example 1. The obtained catalyst is Mn 0.4 Ce 0.1 -MOF / ZSM-5.

[0063] Example 10 The only difference between Example 10 and Example 1 is that the molar ratio of MnCe-MOF to ZSM-5 molecular sieve is 6:10, and the other operations are the same as those in Example 1. The obtained catalyst is Mn 0.48 Ce 0.12 -MOF / ZSM-5.

[0064] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the raw material for preparing the active component in Comparative Example 1 contains only Mn(NO 3 ) 3 Aqueous solution (50%), Ce-free (NO 3 ) 3 6H 2 O.

[0065] The specific operations are: Preparation of MnO as the active component of single-active component HC-SCR catalyst by MOF derivatization methodx 10 mmol Mn(NO 3 ) 3 Aqueous solution (50%) and 12.8 mmolH 2 BDC (terephthalic acid) was added with 96 ml N,N-dimethylformamide and 24 ml anhydrous ethanol and stirred in a beaker for 1 h to fully disperse the solution. The obtained mixed solution was placed in a 250 ml reactor and crystallized in an oven at 100 °C for 12 h under high temperature and high pressure to obtain light yellow solid particles. The obtained solid was centrifuged in a centrifuge tube for 2-3 times, and the lower layer of precipitate was washed and filtered, and repeated 3 times. The obtained precipitate was dried in an oven at 100 °C for 12 h, and then heated to 350 °C in a tube furnace at a heating rate of 5 °C / min and heated with N 2 Calcinate for 3 h, wait for the tube furnace to cool to room temperature, then heat up to 350 °C at a heating rate of 2 °C / min and calcine in air for 3 h. The final sample is recorded as Mn-MOF.

[0066] The active component Mn-MOF prepared by the MOF derivatization method and the ZSM-5 molecular sieve carrier were ground in an agate mortar at a molar ratio of 2:5 for 40 min to obtain the HC-SCR catalyst Mn. 0.4 -MOF / ZSM-5-solid phase grinding catalyst.

[0067] Comparative Example 2 The difference between Comparative Example 2 and Comparative Example 1 is that Comparative Example 2 adopts a precipitation method to prepare the active component MnO of the single active component HC-SCR catalyst. x .

[0068] The specific operations are: Preparation of the active component MnO of the single active component HC-SCR catalyst by precipitation method x 10 mmol of Mn(NO 3 ) 3 Add excess NaOH to the aqueous solution (50%) and adjust the pH to 10. The resulting mixed solution was placed in a 250 ml reactor and crystallized in an oven at 100 °C for 12 h under high temperature and high pressure to obtain purple-black solid particles. The resulting solid was centrifuged in a centrifuge tube for 2-3 times, and the lower layer of precipitate was washed and filtered, and repeated 3 times. The resulting precipitate was dried in an oven at 100 °C for 12 h, and then heated to 350 °C in a tube furnace at a heating rate of 5 °C / min and heated with N 2 Calcine for 3 h, wait for the tube furnace to cool to room temperature, then heat up to 350 °C at a heating rate of 2 °C / min and calcine in air for 3 h. The final sample is recorded as Mn-C.

[0069] The HC-SCR catalyst Mn was obtained by solid phase grinding method by grinding Mn-C and ZSM-5 molecular sieve carrier in a molar ratio of 2:5 in an agate mortar for 40 min. 0.4 -C / ZSM-5 solid phase ground catalyst.

[0070] Comparative Example 3 The only difference between Comparative Example 3 and Comparative Example 1 is that Comparative Example 3 uses a precipitation method to generate the active component Mn-MOF on the ZSM-5 molecular sieve.

[0071] The specific operation is: 10 mmol Mn(NO 3 ) 3 Aqueous solution (50%), 12.8 mmolH 2 BDC (terephthalic acid) and 25 mmol ZSM-5 molecular sieves were added to 96 ml N, N-dimethylformamide and 24 ml anhydrous ethanol and stirred in a beaker for 1 h to fully disperse the solution. The obtained mixed solution was placed in a 250 ml reactor and crystallized at high temperature and high pressure in a 100 ° C oven for 12 h. The obtained solid was centrifuged in a centrifuge tube for 2-3 times, and the lower layer of precipitate was washed and filtered, and repeated 3 times. After the obtained precipitate was dried in an oven at 100 ° C for 12 h, it was heated to 350 ° C in a tube furnace at a heating rate of 5 ° C / min and heated with N 2 Calcinate for 3 h, wait for the tube furnace to cool to room temperature, then increase the temperature to 350 °C at a heating rate of 2 °C / min and calcine in air for 3 h. The final sample is recorded as Mn-MOF / ZSM-5-deposition catalyst.

[0072] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that LaN 3 O 9 6H 2 O replaces Ce(NO 3 ) 3 6H 2 O, and the rest of the operation was the same as in Example 1. The obtained catalyst was recorded as Mn 0.32 La 0.08 -MOF / ZSM-5.

[0073] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that Pr(NO 3 ) 3 6H 2 O replaces Ce(NO 3 ) 3 6H 2 O, and the rest of the operation is the same as in Example 1. The obtained catalyst is denoted as: Mn 0.32 Pr 0.08-MOF / ZSM-5.

[0074] Performance study of the catalysts described in Examples 1 to 10 of the present application and the catalysts described in Comparative Examples 1 to 5: 0.5 mL of the catalysts described in Examples 1-10 and Comparative Examples 1-5 were placed in quartz tubes, respectively, and then placed in a tube furnace. The temperature was set to 150-350°C, and a simulated atmosphere was introduced. NO x =C 3 H 6 =500ppm, O 2 =6%, N 2 The gas volume was balanced, the GHSV was 30000 / h, and the mixed gas velocity was 250 ml / min. The NO in the outlet gas was measured by a flue gas analyzer at 150℃, 200℃, 225℃, 250℃, 275℃, 300℃ and 350℃ for 30 minutes. x and C 3 H 6 The catalytic activity of the catalyst is measured in terms of NO x and C 3 H 6 The removal rate is the evaluation index.

[0075] 1. The effect of adding different rare earth metals on the performance of the catalyst.

[0076] The catalysts described in Example 1 and Comparative Example 1 and Comparative Examples 4-5 catalyze NO x The conversion efficiency of Figure 1 As shown in Figure 2, the catalytic CH conversion efficiency is as follows: Figure 2 shown.

[0077] from Figure 1 and Figure 2 It can be seen that the catalyst described in Example 1 of the present application shows a higher conversion efficiency. In the entire range of 150-350°C, the conversion rate of MnCe-MOF / ZSM-5 is higher than that of Mn-MOF / ZSM-5 (Comparative Example 1) catalyst. At 225°C, the highest conversion rate of 97.26% is achieved, which is higher than that of NO when single metal Mn is used as the active component. x The conversion rate is 90.37%. The HC conversion rates of the two catalysts are both greater than 90% in the entire temperature range, and the trends are not much different. This shows that the introduction of Ce can enhance the NO conversion of Mn-based molecular sieve catalysts. x conversion, which may be attributed to the higher reduction performance of MnCe-MOF / ZSM-5.

[0078] When La active metal components are introduced, the maximum temperature range of MnLa-MOF / ZSM-5 is advanced to 175 °C, and NO x The conversion rate of NO reached 89.84%, but its temperature window was narrow. When the temperature was greater than 175℃, the NO x The conversion rate drops rapidly. This may be because the interaction between La and Mn helps to promote the reaction to move to a lower temperature range, but shortens the temperature range.

[0079] After the introduction of the Pr active component, the conversion rate of MnPr-MOF / ZSM-5 decreased significantly, reaching a maximum conversion rate of only 62.44% at 250°C. This indicates that the interaction between Pr doping and Mn weakens the HC-SCR reaction. In addition, the HC low-temperature conversion rates of MnLa-MOF / ZSM-5 and MnPr-MOF / ZSM-5 catalysts are lower than those of Mn-MOF / ZSM-5. Therefore, when rare earth metal Ce is introduced as the second active component in the Mn-MOF / ZSM-5 catalyst, the redox performance of the catalyst is improved, which increases the conversion rate and broadens the temperature window.

[0080] 2. Effect of the preparation of active components by derivatization and precipitation methods on catalyst performance The catalysts described in Comparative Examples 1 and 2 catalyze NO x The conversion efficiency of Figure 3 As shown in Figure 2, the catalytic CH conversion efficiency is as follows: Figure 4 shown.

[0081] from Figure 3 and Figure 4 It can be seen that in the temperature range of 225-275℃, the NO x The conversion rate is higher than that of Mn-C / ZSM-5 catalyst. And at 225 ℃, Mn-MOF / ZSM-5 catalyst catalyzes NO x The highest conversion rate reached 90.37%, which is much higher than the highest conversion rate of 76.63% of Mn-C / ZSM-5 catalyst at 250 °C. The higher conversion efficiency and wider temperature window indicate that Mn-MOF / ZSM-5 catalyst has better low-temperature HC-SCR performance. At the same time, the HC conversion rate of Mn-MOF / ZSM-5 catalyst reached almost 100% at 225 °C, which is lower than that of Mn-C / ZSM-5, indicating that it has stronger oxidation ability for HC at low temperature. 3 H 6 More full utilization.

[0082] The crystal phase of manganese oxide prepared by MOF derivatization method is mainly in the oxidation state of trivalent manganese, while the crystal phase of manganese oxide prepared by precipitation method is a mixture of trivalent and tetravalent manganese.2 O 3 The catalyst mainly composed of crystalline phase has better low-temperature redox performance and is beneficial to HC-SCR reaction. 0.4 -Mn of MOF / ZSM-5 catalyst 3+ The relative content (79.18%) is much greater than that of Mn 0.4 -C / ZSM-5 catalyst (58.96%). Higher Mn 3+ / Mn 4+ The ratio means that the catalyst has a higher oxygen vacancy density (Ov), which is beneficial to improving the catalytic oxidation efficiency of HC. 0.4 -High Mn of MOF / ZSM-5 catalyst 3+ / Mn 4+ The ratio produces more oxygen vacancies (Ov). The more oxygen defects there are, the faster the oxygen mobility is, thus improving the catalytic performance of the catalyst. Therefore, the active component prepared by the MOF derivatization method is more conducive to the HC-SCR reaction.

[0083] The active components Mn-MOF and Mn obtained in Comparative Example 1 0.4 XRD spectrum of the MOF / ZSM-5 catalyst and the Mn-C of the active component obtained in Comparative Example 2 0.4 -C / ZSM-5 catalyst XRD spectrum Figure 5 shown.

[0084] Mn obtained in Comparative Example 1 0.4 The XPS spectra of Mn 2P of the MOF / ZSM-5 catalyst and the catalyst obtained in Comparative Example 2 are as follows: Figure 6 (a) shown.

[0085] Mn obtained in Comparative Example 1 0.4 -MOF / ZSM-5 catalyst and Mn obtained in Comparative Example 2 0.4 The XPS spectrum of O1s of -C / ZSM-5 catalyst is as follows Figure 6 (b) shown.

[0086] from Figure 5 It can be seen that the crystal phase of manganese oxide prepared by MOF derivatization method is mainly in the oxidation state of trivalent manganese, while the manganese oxide prepared by precipitation method is a mixed state of trivalent and tetravalent manganese. 2 O 3 The catalyst mainly composed of crystalline phase has better low-temperature redox performance and is beneficial to the HC-SCR reaction.

[0087] from Figure 6 (a) It can be seen that in Mn-MOF / ZSM-5 and Mn-C / ZSM-5 catalysts, the Mn element is mainly in the form of Mn3+ (641.9 eV) and Mn 4+ (643.8 eV), MnO may be highly dispersed on the catalyst surface. 3+ / (Mn 3 + + Mn 4+ ) ratio means that the catalyst has a higher oxygen vacancy density (O v ), which accelerates oxygen migration and helps improve the catalytic oxidation efficiency of HC.

[0088] from Figure 6 (b) It can be seen that the Mn prepared by MOF derivatization method 0.4 -Active oxygen on the surface of MOF / ZSM-5 catalyst α The proportion is higher than Mn 0.4 -C / ZSM-5. This may be due to the fact that Mn 0.4 -High Mn of MOF / ZSM-5 catalyst 3+ / (Mn 3+ + Mn 4+ ) ratio produces more oxygen vacancies (O v ), which improves the catalytic performance of the catalyst.

[0089] 3. Effect of solid phase grinding and precipitation methods on catalyst performance The catalysts described in Comparative Examples 1 and 3 catalyze NO x The conversion efficiency of Figure 7 As shown in (a), the catalytic CH conversion efficiency is Figure 7 (b) shown.

[0090] from Figure 7 It can be seen that in the entire temperature test range, the Mn 0.4 The activity of the MOF / ZSM-5 catalyst is much greater than that of the catalyst prepared by the deposition precipitation method. This may be because the active components of the catalyst prepared by the deposition precipitation method are lost too much and unevenly distributed, resulting in low catalytic efficiency.

[0091] In order to further analyze the loading and dispersion of Mn-MOF on the molecular sieve, the micromorphology and structure of the molecular sieve catalysts with different loading methods were analyzed by SEM and EDS.

[0092] Mn prepared in Comparative Example 1 0.4 -SEM image of MOF / ZSM-5- solid phase grinding catalyst Figure 8 As shown in (a), the Mn prepared in Comparative Example 3 0.4 -SEM image of MOF / ZSM-5-deposition catalyst Figure 8(b) shown.

[0093] from Figure 8 (a) shows that in Mn 0.4 -MOF / ZSM-5-solid phase grinding catalyst clearly shows that MnO is evenly dispersed on the large ZSM-5 molecular sieve. x small particles; Figure 8 (b) It can be seen that Mn 0.4 -MOF / ZSM-5-deposition catalyst showed a smooth ZSM-5 molecular sieve surface, and no obvious particles grew on the catalyst surface, which may be due to the Mn 0.4 -MOF is not loaded onto the molecular sieve or enters the pores of the molecular sieve.

[0094] Mn prepared in Comparative Example 1 0.4 -EDS spectrum of MOF / ZSM-5-solid phase grinding catalyst, such as Figure 8 (c) and Figure 8 (d) shown.

[0095] from Figure 8 (c) and Figure 8 (d) It can be seen that the distribution of Mn and O atoms on the catalyst is relatively uniform, indicating that the active component Mn-MOF has good dispersion on the catalyst.

[0096] Comparative Example 3: Mn 0.4 -EDS spectrum of MOF / ZSM-5-deposition catalyst, such as Figure 8 (e) and Figure 8 (f) shown.

[0097] from Figure 8 (e) and Figure 8 It can be seen from (f) that the O atoms on the catalyst are unevenly distributed, and there are only a very small number of Mn atoms on the catalyst.

[0098] from Figure 8 (g) and Figure 8 It can be seen from (h) that the O on the surface of the Mn0.4-MOF / ZSM-5-solid phase grinding catalyst is evenly distributed, while the O on the surface of the Mn0.4-MOF / ZSM-5-deposition precipitation catalyst is aggregated and unevenly distributed.

[0099] In addition, the Mn prepared by ICP-OES calculation results is compared with that of 1 0.4 The mass percentage of Mn atoms in the solid-phase ground MOF / ZSM-5 catalyst is 9.67%. 0.4The mass percentage of Mn atoms in the -MOF / ZSM-5-deposition precipitation catalyst is 5.07%, which indicates that the method of loading Mn-MOF by deposition precipitation will cause too much loss of active components, which also directly leads to the loss of Mn atoms. 0.4 -MOF / ZSM-5-precipitation catalyst compared to Mn 0.4 -The HC-SCR conversion efficiency of the MOF / ZSM-5-solid phase ground catalyst is lower.

[0100] 4. Effect of different ratios of Mn and Ce on Mn x Ce y -Influence of MOF / ZSM-5 catalyst performance (x:y is the molar ratio of Mn and Ce) The catalysts described in Examples 1 to 6 catalyze NO x The conversion efficiency of Fig. 9 As shown in (a), the catalytic CH conversion efficiency is Fig. 9 (b) shown.

[0101] from Fig. 9 (a) and Fig. 9 As can be seen from (b), with the increase of the relative content of Mn, the activity of the catalyst first increases, and when Mn:Ce=4:1, the activity of the catalyst reaches the maximum. This may be attributed to the active component Mn 3+ The content of Ce increases with the increase of Mn ratio, providing more active sites for HC-SCR reaction. When the relative content of Mn continues to increase, the activity decreases. This may be because the increase of Ce ratio leads to Ce 4+ +Mn 3+ →Ce 3+ +Mn 4+ The oxidation reaction of Mn 3+ The content of HC decreases. At the same time, the conversion rate of HC also maintains a high low-temperature removal rate and tends to be stable after the Mn:Ce=4:1 and higher ratios. This may be because the relative proportion of Ce increases, resulting in more Ce 3+ The generation of oxygen vacancies is conducive to the generation of more oxygen vacancies, which accelerates oxygen migration and is beneficial to the oxidation reaction of HC.

[0102] 5. The effect of different ratios of active ingredients to carriers on catalyst performance.

[0103] The catalysts described in Examples 7 to 10 catalyze NO x The conversion efficiency of Fig.10 As shown in (a), the catalytic CH conversion efficiency is Fig.10 (b) shown.

[0104] from Fig.10 (a) and Fig.10It can be seen from (b) that as the active components increase, the catalyst activity also gradually increases. And the growth rate is obvious at first and then slows down. When the active component ratio reaches 4:10, although the activity and temperature range are still improved, the growth is not obvious compared with the previous one, and the catalytic activity has almost reached the peak. This may be because the huge specific surface area of ​​the molecular sieve can be used to load a large amount of active components. When a certain content is reached, the reaction activity of the catalyst has almost reached a certain peak. Because more active components cannot bring higher conversion rates and wider temperature windows, a ratio of 4:10 of active components to molecular sieves is more economical and environmentally friendly.

[0105] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A HC-SCR catalyst, characterized in that: The invention comprises a carrier and an active component loaded on the carrier, wherein the carrier is a ZSM-5 carrier, and the active component is MnCeO x .

2. The HC-SCR catalyst according to claim 1, characterized in that: The molar ratio of the carrier to the active component is (4-10):

2.

3. A composition for preparing an HC-SCR catalyst, characterized in that: It includes a manganese source, a cerium source, terephthalic acid, a ZSM-5 molecular sieve and a solvent; The manganese source includes a 50wt% manganese nitrate solution; the cerium source includes cerium nitrate hexahydrate with a purity of 99.5%; the purity of the terephthalic acid is 99%; and the solvent includes one or two of N,N-dimethylformamide and anhydrous ethanol.

4. The composition according to claim 3, characterized in that The molar ratio of the manganese source to the cerium source is (1-7): 1; and / or, the molar ratio of the total molar amount of the manganese element and the cerium element to the terephthalic acid is 1:(1.0-1.4); And / or, the molar ratio of the manganese source to the ZSM-5 molecular sieve is (2-6):10; And / or, the molar ratio of the manganese source to the solvent is 1:(120-170).

5. The method for preparing the HC-SCR catalyst according to any one of claims 1 to 2, characterized in that: The composition according to claim 3 or 4 is used for preparation.

6. The preparation method according to claim 5, characterized in that: The following steps are involved: (1) mixing the manganese source, the cerium source, the terephthalic acid and the solvent, reacting the mixture, and calcining the reaction product to obtain the active component MnCeO X ; (2) The active component and ZSM-5 molecular sieve are mixed and ground to obtain the HC-SCR catalyst.

7. The preparation method according to claim 6, characterized in that: In step (1), the reaction temperature is 95-120°C and the reaction time is 10-14h; And / or, the calcination includes a first stage calcination and a second stage calcination, wherein the first stage calcination is carried out in a nitrogen atmosphere at a temperature of 300-400°C for 2-4 hours; the second stage calcination is carried out in an air atmosphere at a temperature of 300-400°C for 2-4 hours; and the second stage calcination is carried out after the first stage calcination is completed and cooled to room temperature.

8. The preparation method according to claim 6, characterized in that: The grinding is carried out in an agate mortar; And / or, the grinding time is 30-60 min.

9. A method for treating coke oven flue gas, characterized in that: The reaction is carried out under the action of the HC-SCR catalyst according to any one of claims 1 to 2 or the HC-SCR catalyst obtained by the preparation method according to any one of claims 5 to 8.

10. The method according to claim 9, characterized in that The coke oven flue gas includes one or more of NO, NO2 and C3H6; And / or, the reaction temperature is 150-350°C; And / or, the volume space velocity of the coke oven flue gas is 25000-35000 / h.

Citation Information

Patent Citations

  • Mn-La-Ce catalyst for selective catalytic reduction of NO and application of Mn-La-Ce catalyst

    CN108435238A

  • Composite catalyst and method for catalyzing complete oxidation and elimination of formaldehyde via composite catalyst

    CN112808301A

  • Abatement apparatus and method

    GB202202094D0

  • Catalyst system and method for the reduction of NOx

    US20070092421A1